Acid Suppression Use Among Infants in One Tertiary Children's Hospital in China, 2015–2018: A Retrospective Observational Study - Zhou, Yue; Xu, Lina; Wushouer, Haishaerjiang; Yu, Aichen; Xu, Ziyue; Chen, Chaoyang; Cui, Yimin; Lu, Qinghong; Guan, Xiaodong; Shi, Luwen (Frontiers in Pediatrics, 2021)
Clinical guidelines emphasized that physicians should be cautious when prescribing acid suppressions to infants. Histamine-2 receptor antagonists (H2RAs) and proton pump inhibitors (PPIs) are not approved for use in infants aged below 2 years in China. We investigated H2RA/PPI use in infants aged below 2 years hospitalized between 1st January 2015 and 31st December 2018 in a Chinese tertiary children's hospital. Our study observed that H2RAs/PPIs were frequently prescribed with a prevalence of 4.4% (7,158/162,192). The frequency of PPI use was over two-fold than that of H2RA use (71.9%, 5,148/7,158; 28.1%, 2,011/7,158). H2RAs/PPIs were commonly used to treat infants without digestive system diseases (57.5%, 4,118/7,158). Further studies are urgently needed to evaluate the effectiveness and safety of H2RAs/PPIs in infants.